Is group membership necessary for understanding generalized prejudice? A re-evaluation of why prejudices are interrelated.[article]. - Bergh, Robin
Many scholars have proposed that people who reject one outgroup tend to reject other outgroups. Studies examining a latent factor behind different prejudices (e.g., toward ethnic and sexual minorities) have referred to this as generalized prejudice. Such research has also documented robust relations between latent prejudice factors and basic personality traits. However, targets of generalized prejudice tend to be lower in power and status and thus it remains an open question as to whether generalized prejudice, as traditionally studied, is about devaluing outgroups or devaluing marginalized groups. We present 7 studies, including experiments and national probability samples (N = 9,907 and 4,037) assessing the importance of outgroup devaluation, versus status- or power based devaluations, for understanding the nature of generalized prejudice, and its links to personality. Results show that (a) personality variables do not predict ingroup/outgroup biases in settings where power and status differences are absent, (b) women and overweight people who score high on generalized prejudice devalue their own groups, and (c) personality variables are far more predictive of prejudice toward low-compared with high-status targets. Together, these findings suggest that the personality explanation of prejudice including the generalized prejudice concept is not about ingroups versus outgroups per se, but rather about devaluing marginalized groups. -- (from the authors)
Keywords: Akrami, Nazar; Generalized prejudice; Ingroup biases; Personality; Power; Status